Experimental and Numerical Study of the Effect of Higher Hydrocarbon Content on Laminar Burning Velocity and Flame Stability of Natural Gas. Issue 2 (1st February 2020) - Khan, A.R.; Ravi, M.R.; Ray, Anjan
ABSTRACT: The primary objective of the present work is to systematically study the effect of higher hydrocarbon (HC) content on laminar burning velocity (LBV) and flame stability of various natural gas (NG) blends. Following the central composite design of experiments, proportions of methane, ethane, and propane are varied in the NG blends. All the experiments are performed at 0.1 MPa pressure and 300 ± 3 K temperature using constant pressure outwardly propagating spherical flame method. PREMIX code of CHEMKIN-PRO® is used to compute laminar burning velocities. Experimental results and trends are correlated with an available theoretical expression of LBV based on asymptotic analysis. Presence of higher HC modifies the transport and thermo–kinetic parameters of fuel–air mixtures. The presence of higher HC increases the concentrations of active radicals which ultimately increases the LBV. NG blends have higher burned gas Markstein length compared to pure alkane fuels. Numerical study shows that GRI-3.0 performs well for rich fuel–air mixtures, while predictions of San Diego and USC-II are good for lean fuel–air mixtures. Based on sensitivity analysis and recommendations from the literature, Arrhenius rate parameters of some of the elementary reactions are modified for GRI-3.0 mechanism. Simulations with three variants of the modified GRI-3.0 mechanism show good agreement with the experimental results.